PELATIHAN OLAHRAGA PENCAK SILAT SEBAGAI UPAYA MELESTARIKAN OLAHRAGA ASLI INDONESIA DAN MEWUJUDKAN PRESTASI ANAK PADA USIA DINI DI UPT PENDIDIKAN WILAYAH KECAMATAN CINEAM KABUPATEN TASIKMALAYA - Cucu Hidayat; Deni Setiawan; Defri Mulyana (Jurnal Pengabdian Siliwangi, 2018)
In the era of the increasingly advanced at this time many early childhood is not so familiar with the culture itself because in the era of increasingly advanced globalization makes children prefer to play in more modern areas such as online games that tend to make children become lazy with sports activities such as sports Martial arts that are still not many children / teenagers who want to preserve and develop martial arts as the indigenous culture of the Indonesian Nation, for that we will conduct community service by conducting martial arts training for early childhood, so it can be useful to train children's growth, make Children to be able to have the character of a brave, help each other mutual and can preserve and develop pencak silat as indigenous culture of Indonesia.